Cost-effectiveness of a national quality improvement programme to improve survival after emergency abdominal surgery: Learning from 15, 856 patients. (December 2019) - Yang, Fan; Walker, Simon; Richardson, Gerry; Stephens, Tim; Phull, Mandeep; Thompson, Ann; Pearse, Rupert M.; ,
Abstract: Background: Patients undergoing emergency abdominal surgery are exposed to a high risk of death. A quality improvement (QI) programme to improve the survival for these patients was evaluated in the Enhanced Peri-Operative Care for High-risk patients (EPOCH) trial. This study aims to assess its cost-effectiveness versus usual care from a UK health service perspective. Methods: Data collected in a subsample of trial participants were employed to estimate costs and quality-adjusted life years (QALYs) for the QI programme and usual care within the 180-day trial period, with results also extrapolated to estimate lifetime costs and QALYs. Cost-effectiveness was estimated using incremental cost-effectiveness ratios (ICERs). The probability of being cost-effective was determined for different cost-effectiveness thresholds (£13, 000 to £30, 000 per QALY). Analyses were performed for lower-risk and higher-risk subgroups based on the number of surgical indications (single vs multiple). Results: Within the trial period, QI was more costly (£467) but less effective (−0.002 QALYs). Over a lifetime, it was more costly (£1395) and more effective (0.018 QALYs), but did not appear to be cost-effective (ICER: £77, 792 per QALY, higher than all cost-effectiveness thresholds; probability of being cost-effective: 28.7%–43.8% across the thresholds). For lower-risk patients, QI was more costly and less effective both within trial period and over a lifetime and it did not appear to be cost-effective. For higher-risk patients, it was more costly and more effective, and did not appear cost-effective within the trial period (ICER: £158, 253 per QALY) but may be cost-effective over a lifetime (ICER: £14, 293 per QALY). Conclusion: The QI programme does not appear cost-effective at standard cost-effectiveness thresholds. For patients with multiple surgical indications, this programme is potentially cost-effective over a lifetime, but this is highly uncertain. Highlights: Cost-effectiveness of a quality improvement programme for emergency surgery was assessed. It does not appear cost-effective at standard cost-effectiveness thresholds. It may be cost-effective for patients with multiple surgical indications over a lifetime. There is high uncertainty with the results.